Anti-oxidative and anti-inflammatory effects of 2-cyclopropylimino-3-methyl-1,3-thiazoline hydrochloride on glutamate-induced neurotoxicity in rat brain - Kim, Eun-A; Choi, Jiyoung; Han, A. Reum; Choi, Soo Young; Hahn, Hoh-Gyu; Cho, Sung-Woo (ELSEVIER, 2013)
In a previous in vitro study, we demonstrated the protective effects of a new drug, 2-cyclopropylimino-3-methyl-1,3-thiazoline hydrochloride (KHG26377), against glutamate-induced excitotoxicity in cultured glial cells. In this study, we explored the possible mechanisms underlying the neuroprotective and anti-inflammatory effects of this compound against glutamate-induced excitotoxicity in rat brain. Our results showed that pretreatment with KHG26377 significantly attenuated glutamate-induced elevation of lipid peroxidation, TNF-alpha, IFN-gamma, nitric oxide, reactive oxygen species, NADPH oxidase, and Ca2+ levels, as well as the expression of caspase-3, neuronal nitric oxide synthase, and pERK. Furthermore, KHG26377 pretreatment attenuated key antioxidant parameters such as levels of superoxide dismutase, catalase, glutathione, glutathione peroxidase, and glutathione reductase, and also mitigated suppression of mitochondrial transmembrane potential by glutamate toxicity. Thus, through its antioxidant and anti-inflammatory activities in rat brain, KHG26377 may help protect against glutamate-induced neuronal damage. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: ACTIVATED PROTEIN-KINASES; SIGNAL-REGULATED KINASE; NEURONAL CELL-LINE; OXIDATIVE STRESS; MITOCHONDRIAL DYSFUNCTION; CEREBRAL-ISCHEMIA; NADPH OXIDASE; NITRIC-OXIDE; PROVIDES NEUROPROTECTION; MEDIATED NEUROTOXICITY